(3GSJNOGe GdajOjhgGJ GdSGNQI HTHcGJ GdJhGUd GdGLJeGYi ddJYHjQ Yf GJLGgGJ GdTHGH GdeUQi fMh GdbVGjG GdeLJeYjI (B/ s - (3EjeGf fhQ GdOjf YHOGdYRjR YWjg ESeGYjds; (3hdjO aJM Gddg HQcGJ (B: s ((3GdbGgQI (B: s (3EjeGf fhQ GdOjf YHOGdYRjR YWjg ESeGYjd (B: s, 2021)
(3gOaJ gPg GdOQGSI Edi OQGSI GdajOjhgGJ GdSGNQI HTHcGJ GdJhGUd GdGLJeGYi; h Pdc ef CLd Gdhbha Ydi CSHGH GdGSJNOGe(B: (3h Edi Ci eOi JYHQ GdajOjhgGJ GdSGNQI Yf GJLGgGJ GdTHGH GdeUQi fMh GdbVGjG GdeLJeYjI(B: (3h cPdc Edi Ci eOi jSJNOegG GdTHGH GdeUQi ddJYHjQ Yf GJLGgGJge fMh GdbVGjG GdeLJeYjI(B. (3h bO GYJeOJ GdOQGSI Ydi GdefgL GdeSMi HTbjg GdejOGfi h GdJMdjdi(B: (3h Pdc HGSJNOGe UMjaI GdGSJHjGf cCOGI HMKjI HGdJWHjb Ydi (B418 (3eaQOI Je GNJjGQgG HWQjbI YeOjI; h cPdc HGSJNOGe GSJeGQI JMdjd eVehf Je JMdjd cGaI GdajOjhgGJ GdefThQI NdGd GdaJQI ef (B1(3jfGjQ (B2020 (3h MJi (B30 (3jhfjh (B2020 (3HELeGdi (B596 (3ajOjh(B: (3ai eMGhdI ddJYQa Ydi edGeM h CHYGO GdUhQI GdEYdGejI GdJi JfTQgG ajOjhgGJ GdYjfI JLGg GdbVGjG GdJi JJfGhdgG h Gdbje GdeJVefI HgG(B: (3h ajeG jdi Cge fJGFL GdOQGSI GdejOGfjI(B: (3CXgQJ fJGFL GdOQGSI GdejOGfjI Cf ZGdHjI GdeHMhKjf jYHQhf Yf GJLGgGJge fMh GdbVGjG GdeLJeYjI ef NdGd GdajOjhgGJ GdSGNQI HOQLI eJhSWI HfSHI (B79.7%. (3GJabJ cd ef GdOQGSI GdJMdjdjI h GdejOGfjI Ydi Cf GdbVGjG GdWHjI cGfJ Ydi bGFeI ChdhjGJ GdGgJeGe GdLeGgjQi h GdEYdGei NdGd GdfUa GdChd ef YGe (B2020. (3CXgQJ fJGFL GdOQGSI GdJMdjdjI GMJhGA GdajOjhgGJ GdSGNQI Ydi GdYOjO ef Gdbje GdEjLGHjI JCJi ai ebOeJgG (B"(3cTa GdJLGhRGJ(B": (3jdjgG (B"(3GdJQajg h GdacGgI(B" (3h JJab gPg GdfJjLI eY eG JhUdJ Edjg GdOQGSI GdejOGfjI(B. (3CXgQJ fJGFL GdOQGSI GdJMdjdjI GMJhGA GdajOjhgGJ GdSGNQI Ydi GdYOjO ef Gdbje GdSdHjI JCJi ai ebOeJgG (B"(3YOe GMJQGe GdBNQ(B": (3jdjgG (B"(3GdYfa(B": (3JJab gPg GdfJjLI eY eG CXgQJg GdOQGSI GdejOGfjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdEYdGe (B- (3bSe GdEPGYI h GdJdjaRjhfs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GJLGgGJ GdTHGH GdeUQis; (3GdajOjhgGJ GdSGNQIs; (3THcGJ GdJhGUd GdGLJeGYis